Technology and education: theoretical reflections exemplified in Religious Education. Issue 3 (1st September 2016) - Reader, John; Freathy, Rob
Abstract: How do recent technological advances impact upon the field of education? This article examines the work of the philosopher of technology Bernard Stiegler and his interpretation of technology as pharmakon (both remedy and poison). This is linked to threshold concept theory which advocates more creative ways of learning, and illustrated through a practical example from a new approach to Religious Education (RE). It will be argued that it is possible to construct educational assemblages more conducive to personal and spiritual development.